PEMBELAJARAN SEJARAH PADA PROGRAM KEJAR PAKET C - Windarsari, Ranulin; Sunardi, Sunardi; Djono, Djono (Paramita: Historical Studies Journal, 2017)
This study is aimed to describe the implementation of learning history in Kelompok Belajar (learning group) or Kejar Paket C programs. This study uses the descriptive qualitative method. Data were collected by interviews, documentation, and observation. Data analysis technique use qualitative analysis inductive models with purposive sampling technique. The results of this study are: first, planning learning history in Kejar Paket C program started from In House Training for educators in Kejar Paket C program which practiced in the preparation of the learning device are appropriate to the curriculum; second, the implementation of learning history in Kejar Paket C program involves three patterns of learning consisting of 20% face-to-face interaction, 30% tutorials, and 50% independent activity; third, constraints in the implementation of history learning in Kejar Paket C program is the readiness of learners in receiving learning materials, learning infrastructure, and the competence of educators in conveying the teaching of history; fourth, evaluation of learning history in Kejar Paket C program is equal to the formal school.Â Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan pembelajaran sejarah pada program Kejar (kelompok belajar) Paket C. Penelitian ini menggunakan metode deskriptif kualitatif. Pengumpulan data dilakukan melalui wawancara, dokumentasi dan observasi. Teknik analisis data yang digunakan adalah analisis kualitatif model induktif dengan teknik purposive sampling. Hasil penelitian antara lain: pertama, perencanaan pembelajaran sejarah pada program Kejar Paket C dimulai dari pelatihan In House Training bagi para pendidik program Kejar Paket C yang dipraktikan dalam penyusunan perangkat pembelajaran yang disesuaikan dengan KTSP; kedua, pelaksanaan pembelajaran sejarah pada program Kejar Paket C meliputi tiga pola pembelajaran yang terdiri dari tatap muka 20%, tutorial 30%, dan kegiatan mandiri 50%; ketiga, kendala pelaksanaan pembelajaran sejarah pada program paket C adalah kesiapan peserta didik dalam menerima materi pembelajaran, sarana prasarana pembelajaran, serta kompetensi pendidik dalam menyampaikan pembelajaran sejarah; keempat, Evaluasi pembelajaran sejarah pada program Kejar Paket C sama dengan sekolah formal.Â